Development of Spinal Tuberculosis in an Adolescent With Crohn's Disease After Infliximab Therapy: A Case Report With Literature Review - Jung, Jae Hoon; Choi, Sujin; Kang, Youra; Cho, Dae-Chul; Lee, So Mi; Park, Tae In; Choe, Byung-Ho; Kim, Dongsub; Kang, Ben (Frontiers in Pediatrics, 2022)
Introduction: Tuberculosis (TB) spondylitis, also known as Pott’s disease, is a severe form of extrapulmonary TB. Infliximab treatment for Crohn’s disease (CD) patients increases the risk of TB, and is likely to increase the risk of TB spondylitis as well. Case presentation: We report a rare case of TB spondylitis development in a 16-year-old female with CD. She had a close household contact of active pulmonary TB and received contact investigation. She was diagnosed with latent TB 1 month before the diagnosis of CD, and had started a latent TB treatment regimen with isoniazid for 9 months. At 5 months from the start of latent TB treatment, infliximab was started. Approximately 1 year after infliximab treatment, her infusion interval was shortened from every 8 weeks to every 4 weeks owing to secondary loss of response due to nonimmunogenic pharmacokinetic failure. One month later, miliary TB developed and infliximab was stopped. She received a miliary TB treatment regimen for 6 months, curing the disease. Three months later, spinal TB was incidentally detected on abdominal computed tomography. She received a TB treatment regimen for 12 months, curing spinal TB. Currently, she is receiving vedolizumab to treat CD and is in clinical remission. Although this patient has sufficiently been treated at each stage of TB development, particularly for latent TB and miliary TB, TB spondylitis still developed. Conclusion: Considering that TB spondylitis developed despite sufficient treatment at each stage, pediatric gastroenterologists should stay cautious when using anti- tumor necrosis factor agents in patients with inflammatory bowel disease with a history of latent TB.